SOLAR ACTIVITY MONITORING FOR THE PERIOD MARCH 20-25, 2019 - Sarsembayeva, A.T.; Odsuren, M.; Belisarova, F.B.; Sarsembay, A.T.; Abyshev, M.E. (Academic Scientific Journal of Computer Science, 2020)
During a large solar flare, the flux of hard electromagnetic radiation from the sun increases many times. In the ultraviolet (UV), X-ray and gamma rays that are invisible to us, our Sun becomes “brighter than a thousand suns”. Radiation reaches the Earth’s orbit eight minutes after the solar flare. In a few tens of minutes, flow of charged particles arrive, accelerated to gigantic energies, and after two or three days - huge clouds of solar plasma. The huge interest in solar flares is not accidental. Large flares have a strong effect on near-Earth outer space. Particle and radiation flows are dangerous for astronauts. In addition, they can damage the electronic devices of spacecraft, disrupt their work. UV and X-rays from a flash suddenly increase ionization in the upper atmosphere of the Earth, in the ionosphere. This can lead to radio communications disruptions, malfunctions of the radio navigation devices of ships and aircraft, radar systems, and long power lines. The source of flare energy is a magnetic field in the atmosphere of the Sun. It determines the morphology and energy of the active region where the flare will occur. Here, the field energy is much larger than the thermal and kinetic energy of the plasma. During a solar flare, the excess field energy is rapidly converted to particle energy and plasma changes. The physical process that provides this transformation is called magnetic reconnection. In this paper was monitored solar flares registered in the period 20-25 March 2019. We measure physical parameters of 2 flares, such as the temporal scale, size, and magnetic flux density, and find that the sizes of flares tend to be distributed more broadly as the GOES class becomes weaker and that there is a lower limit of magnetic flux density that depends on the GOES class. We also made a brief analysis of solar flares registered in these days, also has shown the duration of time and peak of solar flares in Universal time. We have identified several physical quantities of solar flares and estimated reconnection rate of solar flares. To determine the physical parameters we used images taken with the AIA instrument on board SDO satellite at wavelengths 131 Å, 174 Å, 193 Å, 211 Å, 335 Å, 1600 Å, 1700 Å, 4500 Å, SXT - pictures, HMI Magnetogram, SOLIS Chromospheric Magnetogram, GOES XRT-data. We estimate reconnection inflow velocity, coronal Alfven velocity, and reconnection rate using the observed values. The inflow velocities are distributed from a few km s-1 to several tens of km s-1, and the Alfven velocities in the corona are in the range from 103 to 104 km s-1. Hence, the reconnection rate is 10-3. We find that the reconnection rate in a flare tends to decrease as the GOES class of the flare increases.